Colloidal Co single-atom catalyst: a facile synthesis strategy and high catalytic activity for hydrogen generation. Issue 4 (28th January 2020) - Wang, Junkai; Huang, Zhenxia; Lu, Lilin; Jia, Quanli; Huang, Liang; Chang, Shuai; Zhang, Mingyang; Zhang, Zuotai; Li, Sun; He, Dongsheng; Wu, Wenhao; Zhang, Shaowei; et al.
Abstract : A facile route for on-demand hydrogen production via simply controlling the mixing process of a KBH4 solution and an aqueous solution of ISOBAM-104 stabilized Co 2+ ions. Abstract : Developing highly active single-atom catalysts is one of the most significant issues for future renewable energy technologies. Here we present a facile but effective and efficient strategy for synthesizing colloidal Co single-atom catalysts with excellent catalytic activity using a copolymer, poly(isobutylene- alt -maleic anhydride) (ISOBAM-104), as a stabilizing agent. The catalytic activity of the as-prepared colloidal single-atom catalyst for hydrogen generation from hydrolysis of KBH4 in an alkaline solution was as high at about 14 300 mL-H2 min −1 g-Co −1, which was even higher than that of its Pt, Pd or Rh counterpart. Such a high catalytic activity of the colloidal catalyst was attributable to the in situ formed and well-stabilized Co single-atoms whose existence was confirmed by aberration-corrected high-angle annular dark-field scanning transmission electron microscopy. Moreover, quantum chemical calculations reveal that ISOBAM-104 has a higher binding energy with the Co catalyst than with the well-known conventional protective agents, including poly( N -vinyl-2-pyrrolidone), starch, carboxymethylcellulose sodium, polyvinyl alcohol, sodium polyacrylate and polyethylene glycol. In addition, the use of as-prepared Co catalysts resulted in a much lowered barrier for the dissociation reaction of BH4 − than in the cases of using Pt, Pd and Rh counterpart catalysts.